Adaptation Patterns of Corn Farmers to Climate Change - Farizah Dhaifina Amran; Tsalis Kurniawan Husain; Andi Azrarul Amri; Dwi Prasetyawati Thana (Agribusiness Journal, 2024)
The extreme climate change on the earth's surface in recent years is a serious issue. Agricultural sector has been affected by climate change because it causes crop failure and decreases crop productivity, especially food crops, namely corn. The climatic conditions of the Takalar Regency are generally characterized by high rainfall and drought, particularly at dry times. The purpose of this study is to: (1) Analyze the opinions of corn farmers; (2) Analyze the adaptation pattern of corn farmers; (3) Analyze the factors that influence the adaptation pattern of corn farmers. The first and second objectives were analyzed descriptive quantitatively, and the third objective was analyzed using ordinal logistic regression. The results on 39 farmers being interviewed showed that (1) Corn farmers' opinions regarding changes in temperature, rain intensity, drought have increased in recent years; (2) Adaptation patterns carried out by corn farmers in facing climate change are improving water management, soil management technology, integrated pest control, changing cropping patterns, and adjusting planting time; (3) Factors that affect the pattern of adaptation of corn farmers to climate change are land area, number of dependents of the household head, income, and access to information on climate change.